SOME NOTABLE DIVERGENCES IN THE DEVELOPMENT OF SOUTH AFRICAN AND NAMIBIAN INSOLVENCY LAW - André Boraine (Obiter, 2021)
It is a well-known fact that the legal systems of South Africa and Namibia, or rather the former South West Africa, were rather identical until the advent of independence of the latter on 21 March 1990. This note thus deals with aspects of the development of insolvency law in South Africa and Namibia since Namibia became independent. What is also important is the fact that both Namibia and South Africa adopted a constitution that is based on a Bill of Rights (see the Constitution of the Republic of Namibia of 1990 and the South African Constitution of 1996). Some developments in insolvency law based on these features are therefore also considered in this note. As indicated, upon independence Namibia retained significant portions of South African law including its legislation. Owing to the shared background of Roman-Dutch-law and English-law influences, both Namibia and South Africa can still be classified as having mixed legal systems. Like South Africa, Namibian insolvency law is not contained in one single statute although it is still largely regulated by the South African inherited Insolvency Act 24 of 1936 (hereinafter “the Insolvency Act”), which deals first and foremost with the sequestration of individuals and related matters. Namibia also inherited the South African Companies Act 61 of 1973 but the South African Close Corporations Act 69 of 1984 was largely adopted as the Close Corporation Act 26 of 1988 that came into operation on 25 July 1994. These pieces of legislation, amongst others, deal with the liquidation or winding-up of companies and close corporations respectively. Apart from these statutory enactments, precedents and common-law principles also apply in the absence of specific statutory provisions. The Insolvency Act of 1936, however, remains the principal source of both South African and Namibian insolvency law and the other enactments render certain provisions of the Insolvency Act applicable. At present and as far as the principles are still comparable, precedents set by South African and Namibian courts remain relevant in both jurisdictions. In order to align some of the terminology with structures and developments in Namibia, the 1936 Insolvency Act was amended in a number of respects by the Namibian Insolvency Amendment Act 12 of 2005. The wording of the Insolvency Act was also thereby amended to make it gender-friendly. However, when dealing with either system it is important to ascertain to what extent statutes that applied in both jurisdictions have been adopted, subsequently amended and/or replaced. The Namibian government has for instance introduced a new Companies Act 28 of 2004 that is bound to replace the South African-based Companies Act of 1973. Although a new insolvency statute is not in the pipeline in Namibia, an amendment act to the 1936 Insolvency Act has been published during 2005 (the 2004 Companies Act was assented to on 19 December 2004 but it will only come into operation once so proclaimed). In South Africa a new Companies Act 71 of 2008 has been introduced but it is also still due to come into operation. New insolvency legislation that will unify the insolvency of individuals and companies is on the table in South Africa but it is not clear when this process will come to fruition. Another general feature is that judgments of the South African and Namibian high courts are clearly still influential in both jurisdictions but as amendments and separate legal developments will deviate from the former common norm, judgments will clearly have to be treated with circumspect in future. In the absence of a comprehensive textbook dealing with the Namibian version of insolvency law, South African textbooks will remain of some use to that jurisdictions but also subject to the same qualifications expressed above.